Safety reporting study of nonsteroidal anti-inflammatory drugs in a tertiary care teaching hospital, SIMS, Uttar Pradesh - Dey, Saborni; Kumar, Harsh; Shukla, Anand Kumar (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most frequently used drugs to treat pain and inflammation. Although NSAIDs are having enormous clinical use, but are not devoid of adverse drug reactions (ADRs) as peptic ulcer, gastritis, renal, neurological reactions etc. So, this pilot study is intended to assess the incidence and pattern of ADRs of the NSAIDs in a tertiary care teaching hospital. Methods: Total 600 Orthopaedic out-patients of SIMS, Hapur were enrolled in the study to observe the risk of ADRs due to NSAIDs. All the ADRs were further analysed in relation to age, sex, types of drug and its pattern etc. The causality was analysed by using Naranjo’s Algorithm and severity was analysed by using the Hartwing and Siegel scale. Results: Out of the 600 patients with NSAID therapy, 35 patients (5.83%) experienced total 10 types of ADRs. The adverse drug reactions observed by the patients were gastric symptoms, headache, urticaria, oedema etc. The most frequently observed ADR was gastritis. With all the prescribed drugs Tab Diclofenac sodium accounted for 57.14% and Paracetamol for 11.42% of all the ADRs. According to Naranjo’s Algorithm 62.87% ADRs were possible’ and 37.14% were of probable type and ADRs were mostly mild in severity. Conclusion: In this study, incidence of adverse reactions to nonsteroidal anti-inflammatory drugs was 5.83 and the most common implicated drug for the ADRs were Diclofenac sodium. Most of the adverse effects were mild and tolerable.